Vietnam-U.S. Bilateral Trade Agreement. (U.S. Congressional Research., 2002)
Provides an overview of the July 2000 U.S.-Vietnam trade agreement. Examines Congressional role in normalization of U.S.-Vietnam trade relations, reviews U.S. and Vietnamese interests in a trade agreement, and explains Vietnam's ambivalence toward economic integration.